Characterizing the development of photosynthetic capacity in relation to chloroplast structure and mineral nutrition in leaves of three woody fruit species. (22nd November 2021) - Fu, Xinyu; Zhang, Jingyi; Zhou, Linyao; Mo, Weiping; Wang, Huicong; Huang, Xuming
Abstract: Plants have evolved different developmental patterns of photosynthetic capacity to better adapt to changing environmental conditions. Natural variation in photosynthetic development offers great potential for improving crop productivity. In this study, leaf developmental patterns were characterized in three woody fruit tree species with distinct photosynthetic capacity and growth habits. Changes in the photosynthetic rate, photosystem II (PSII) efficiency, chloroplast ultrastructure, activities of photosynthetic enzymes, and contents of carbohydrates and mineral nutrients were examined at five developmental stages to explore the interspecific variation in photosynthetic development. Rapid development of photosynthetic machinery and high photosynthetic capacity were found in Indian jujube ( Ziziphus mauritiana ) and apple ( Malus domestica ), whose net CO2 assimilation rate ( A ) peaked at full leaf expansion (FLE). Litchi ( Litchi chinensis ), a delayed-greening species, showed slow development of photosynthetic competence, with A peaked after FLE. The low photosynthetic capacity of litchi during early leaf expansion was associated with its delayed chloroplast development, low accumulation of starch, and low activities of ribulose-1, 5-bisphosphate carboxylase/oxygenase and NADP-glyceraldehyde-3-phosphate dehydrogenase. Correlations between mineral contents and A across leaf stages and species identified manganese as the rate-limiting nutrients in photosynthetic development in new leaves. Foliar spray of MnSO4 solution (1 g l −1 ) induced a short-term increase in photosynthesis in young leaves of litchi. These findings suggest that a better understanding of interspecific variation in photosynthetic development facilitates the development of new strategies for improving the photosynthetic efficiency of woody fruit trees.